The Politics of Aesthetics - Rancière, Jacques 1940- (London Continuum, 2004)
The Politics of Aesthetics rethinks the relationship between art and politics, reclaiming "aesthetics" from the narrow confines it is often reduced to. Jacques Rancière reveals its intrinsic link to politics by analysing what they both have in common: the delimitation of the visible and the invisible, the audible and the inaudible, the thinkable and the unthinkable, the possible and the impossible. Presented as a set of inter-linked interviews, The Politics of Aesthetics provides the most comprehensive introduction to Rancière's work to date, ranging across the history of art and politics from the Greek polis to the aesthetic revolution of the modern age. Already translated into five languages, this English edition of The Politics of Aesthetics includes a new afterword by Slavoj Zizek, an interview for the English edition, a glossary of technical terms and an extensive bibliography.
Keywords: 21st Century (2001-2100); Esthetics; Philosophy; Politics; France